Answer:
![2x^2y[x^{2}y^{2}-6xy-4]](https://tex.z-dn.net/?f=2x%5E2y%5Bx%5E%7B2%7Dy%5E%7B2%7D-6xy-4%5D)
Step-by-step explanation:
we have
![2x^{4}y^{3}-12x^3y^2-8x^2y](https://tex.z-dn.net/?f=2x%5E%7B4%7Dy%5E%7B3%7D-12x%5E3y%5E2-8x%5E2y)
Factor ![2x^2y](https://tex.z-dn.net/?f=2x%5E2y)
so
![2x^2y[x^{2}y^{2}-6xy-4]](https://tex.z-dn.net/?f=2x%5E2y%5Bx%5E%7B2%7Dy%5E%7B2%7D-6xy-4%5D)
Answer:
its B ITHINK
Step-by-step explanation:
Answer:
y = ![\frac{b}{1-m}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%7D%7B1-m%7D)
Step-by-step explanation:
In order to get <em>y</em> by itself, we need to pull <em>y</em> out of 1 and <em>m </em>on the right side.
b = y(1 - m) since y(1 - m) is the same as y - my.
Once we have pulled <em>y</em> out of 1 and m, we can divide both sides by 1 - m
= ![\frac{y(1 - m)}{1 - m}](https://tex.z-dn.net/?f=%5Cfrac%7By%281%20-%20m%29%7D%7B1%20-%20m%7D)
We can cancel out the 1 - m on the right side since (1 - m) / (1 - m) = 1
Finally we get our answer:
= y
This is the same as y = ![\frac{b}{1-m}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%7D%7B1-m%7D)